HUBUNGAN ANTARA SELF CARE DENGAN KESEHATAN MENTAL PADA REMAJA DI SMA ISLAM DIPONEGORO WAGIR - Jelita, Angelina Marissa; Rosdiana, Yanti; Trishinta, Sirli Mardianna (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
The issue of mental health among adolescents in Indonesia is often a concern. One of the contributing factors to mental health problems in Indonesia is the lack of understanding in practicing self-care for mental health. The aim of the research is to determine the relationship between self-care and mental health among adolescents at SMA Islam Diponegoro Wagir. The research design used is correlational. The research population consists of 115 students at SMA Islam Diponegoro Wagir, with a sample size of 89 individuals. The sample was taken using a simple purposive sampling technique. Data was collected using the Mifdul Self Care Scale (MSCS) questionnaire and the Mental Health Continuum-Short Form (MHC-SF). Data analysis used univariate cross-tabulation tests and bivariate Chi-Square. The results of the univariate cross-tabulation test showed that the majority of 79 (88.8%) of the adolescents in SMA Islam Diponegoro Wagir had a sufficient level of self-care, while regarding mental health, most 75 individuals (84.3%) of the adolescents in SMA Islam Diponegoro Wagir need serious attention as most of the adolescents have a low level of mental health. The Chi Square test shows that there is a significant relationship between self-care and mental health in adolescents at SMA Islam Diponegoro Wagir. This is evidenced by a p-value of 0.017, which is less than the significance level (α) of 0.05. Therefore, it can be concluded that self-care has a significant relationship with mental health in adolescents, indicating that self-care plays an important role in maintaining mental health among adolescents at SMA Islam Diponegoro Wagir.